USING ROLE PLAY METHOD TO IMPROVE STUDENTS’ SPEAKING SKILLS AT SENIOR HIGH SCHOOL - Ona Marta Iyarmasa; Muliaty Ibrahim; Abdul Malik Iskandar; Muhamad Yahrif (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Ona Marta Iyarmasa, 2025. Using the Role Play Method to Improve Students' Speaking Skills at Senior High School (Supervised by Muliaty Ibrahim and Abdul Malik Iskandar). This study aims to examine the effect of using the role play method on the speaking skills of eleventh-grade students at SMA Negeri 13 Makassar in the 2024/2025 academic year. The research design employed a quasi-experimental method with a quantitative approach. The study population consisted of 72 students divided into two classes: a control class and an experimental class. The research involved administering a pre-test and post-test, followed by four treatment sessions using the role play method. Data were collected through the pre-test and post-test, in which students' speaking performance scores were evaluated. The results showed that the average pre-test score of the control group was 63.00, increasing to 73.50 in the post-test. In the experimental group, the average pre-lest score was 68.36, rising to 78.86 in the post-test. There was a significant difference in the mean scores of the experimental class, with an increase of 7.9 points after the treatment. The significance level was 0.000 < 0.05, indicating that the null hypothesis (HO) was rejected and the alternative hypothesis (HI) was accepted. Based on these findings, it can be concluded that the use of the role play method significantly improved the speaking skills of eleventh-grade students (classes XI-5 and XI-6) at SMA Negeri 13 Makassar.